An Empirical Study on the Determinants of Corporate Cash Holdings – Evidence from China - Shang, Jie-Chen (2016)
This study investigates the determinants of corporate cash holdings in Chinese market. After examining a panel data set obtained from 207 Chinese listed companies over the period 2004 to 2015, we find evidence that firms paying dividends prefer to accumulate more cash. At the same time, larger firms, firms with larger net working capital, firms with greater capital expenditures and firms with higher level of leverage tend to hold less cash. On the other hand, the relationship between cash holdings and growth opportunities is ambiguous, so does the relationship between cash holdings and cash flow. Our findings are generally in support of the trade-off theory. Both transaction and precautionary motives play important roles in explaining the determinants of cash holdings for Chinese listed companies.